2014
DOI: 10.1371/journal.pone.0110790
|View full text |Cite
|
Sign up to set email alerts
|

Acid Suppression Therapy Does Not Predispose to Clostridium difficile Infection: The Case of the Potential Bias

Abstract: ObjectiveAn adverse effect of acid-suppression medications on the occurrence of Clostridium difficile infection (CDI) has been a common finding of many, but not all studies. We hypothesized that association between acid-suppression medications and CDI is due to the residual confounding in comparison between patients with infection to those without, predominantly from non-tested and less sick subjects. We aimed to evaluate the effect of acid suppression therapy on incidence of CDI by comparing patients with CDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
0
37
1
5
Order By: Relevance
“…Given that disruption of the intestinal flora persists for >3 months after antibiotic therapy, patients can remain susceptible to CDI development long after ending the treatment 28 . Acid suppression by proton pump inhibitors (commonly used for dyspepsia, peptic ulcer disease and gastroesophageal reflux disease) has frequently been associated with CDI 158,159 but the precise role of proton pump inhibitors in CDI (and a causal relationship) remains unclear 160,161 . Of all patients with antibiotic-associated diarrhoea, 20–30% is caused by C. difficile 162 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Given that disruption of the intestinal flora persists for >3 months after antibiotic therapy, patients can remain susceptible to CDI development long after ending the treatment 28 . Acid suppression by proton pump inhibitors (commonly used for dyspepsia, peptic ulcer disease and gastroesophageal reflux disease) has frequently been associated with CDI 158,159 but the precise role of proton pump inhibitors in CDI (and a causal relationship) remains unclear 160,161 . Of all patients with antibiotic-associated diarrhoea, 20–30% is caused by C. difficile 162 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In general, gastric acid suppression is believed to aid the reach of more vegetative organisms to the colon; however, the spores of C. difficile are acid-resistant and capable of remaining viable at the low pH gastric juice. Although some investigators have reported the increase in risk of CDI with acid suppression [28], the others have not agreed with this [37,46]. A study investigating CDI in patients aged 67 to 92 years old observed that all of these patients were non-surgical and haemodialysis and intensive care unit stay were not risk factors [39].…”
Section: Year Finding Reportedmentioning
confidence: 99%
“…Studije koje su se do sada bavile ispitivanjem potencijalne veze između CDAD i lekova koji smanjuju lučenje hlorovodonične kiseline, pre svega inhibitora protonske pumpe, često su dolazile do potpuno kontradiktornih rezultata. Dok su neki autori sugerisali na povezanost primene ovakve terapije sa CDAD, drugi su nakon određenih prilagođavanja potpuno negirali postojanje takve veze [39,40].…”
Section: Lekovi Kao Faktori Rizika Za Nastanak Infekcije Udružene Sa unclassified